1980
DOI: 10.7601/mez.31.73
|View full text |Cite
|
Sign up to set email alerts
|

Pheromone study on acarid mites IV : Citral : composition and function as an alarm pheromone and its secretory gland in four species of acarid mites

Abstract: Through bioassay and biolegical investigations on the alarm pheromone of five species of acarid mites, Alettroglyphzts ovattes, CZirpoglt!phus lactis, Lardbglyphus konoi and Dermatophagoides forinae. following results were obtained. Citral and nery1 formate were more er less active as an alarm pheromone and not strictly species-specific within five species. Along with T. Putrescentiae, two more acarid mites, C lactis and L. konoi, were concluded to possess the alarm pheromone and citral was identified as their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…We have defined the alarm pheromone as follows; the escaping behavior is evoked with a disturbance by patting with a soft drawing brush or squashing one or several mites, and the same observation is reproducible on exposure of the mite volatile (Kuwahara et al, 1980b).…”
Section: Discussionmentioning
confidence: 99%
“…We have defined the alarm pheromone as follows; the escaping behavior is evoked with a disturbance by patting with a soft drawing brush or squashing one or several mites, and the same observation is reproducible on exposure of the mite volatile (Kuwahara et al, 1980b).…”
Section: Discussionmentioning
confidence: 99%
“…Five species use the compound as their alarm pheromone: Carpoglyphus lactis, Lardoglyphus konoi (Kuwahara et al, 1980b), Suidasia medanensis (Leal et al, 1989d), Glycyphagus domesticus (Kuwahara et al, 1991), Schwiebea elongata . However, this is the first example identifying the function of neral as the female sex pheromone.…”
Section: Discussionmentioning
confidence: 99%
“…Other than alarm pheromones, sex and aggregation pheromones are also present as the same gland components of Astigmata (Kuwahara et al, 1980;Mizoguchi et al, 2003), and it is reasonable to understand that each species can handle a kind of pheromone function within the three. Recently, it has been realized that a species of mites can manipulate at least two kinds of pheromones (Kuwahara, 2001), such as found in Rhizoglyphus robini where a combination of the alarm and sex pheromones (neryl formate and α-acaridial, respectively) present in the same gland is manipulated to show each own function (Mizoguchi et al, 2003), and as found in Schwiebea elongata where neral functions not only as an alarm pheromone at a high dose but also as an attractant at a low dose, possibly an aggregation pheromone (Nishimura et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical structures of the pheromones so far known are classified into three groups; 1) monoterpenes, 2) aromatics and 3) hydrocarbons (Kuwahara, 1999). The monoterpenes consist of five compounds; neryl formate in six species [four species belong to the genus Rhizoglyphus (Akiyama et al, 1997), Tyroborus lini (Tomita et al, 2003), and Tyrophagus putrescentiae (Kuwahara et al, 1975)], neral in five species [Carpoglyphus lactis (Kuwahara and Suzuki, 1983), Glycyphagus domesticus (Kuwahara et al, 1991a), Suidasia medanensis , Lardoglyphus konoi (Kuwahara et al, 1980) and Schwiebaea elongata ], geranial in Histiostoma laboratorium (Kuwahara et al, 1991b), isopiperitenone in Tyrophagus similis (Kuwahara et al, 1987) and β-acaridial in Tyrophagus longior (Noguchi et al, 1998). The aromatic compound 2-hydroxy-6-methylbenzaldehyde functions as the pheromone in Tyrophagus perniciosus (Leal et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation